Introduction to Economics - Rossignoli, Cristiano (WorldFish, 2022)
Economics is a science, and just like other sciences, it deals with a fundamental problem of nature. Economics is the branch of knowledge concerned with the production, consumption and transfer of wealth. It is the study of how scarce resources are allocated to fulfill the infinite wants of consumers.